Salivary alpha amylase and cortisol levels in children with global developmental delay and their relation with the expectation of dental care and behavior during the intervention - Santos, Márcio José Possari dos [UNESP]; Bernabé, Daniel Galera [UNESP]; de Melo Stevanato Nakamune, Ana Claudia [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Coelho Avila de Aguiar, Sandra Maria Herondina [UNESP]; Oliveira, Sandra Helena Penha de [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
The purpose of this study was to analyze the alpha-amylase (sAA) and cortisol levels in children with Global developmental delay (GDD) before and after dental treatment and its association with the children's behavior during treatment. The morning salivary cortisol levels and activity of sAA of 33 children with GDD were evaluated before and after dental treatment and were compared to 19 healthy children. The behavior of children with GDD during dental care was assessed by the Frankl scale. Children with GDD showed lower levels of sAA activity than healthy children, but this result was not significant. The salivary cortisol levels were similar between GOD and healthy children. GDD children showed increased levels of sAA (but not cortisol) prior to the dental treatment as compared to the post-treatment phase. GOD children who showed less favorable behavior during dental care had higher levels of sAA and salivary cortisol than GOD children with more favorable behavior, but only the sAA results were significant. In conclusion, GOD children show hyperactivity of the SNS-axis in anticipation of dental treatment which indicates the need for strategies to reduce their anxiety levels before and during dental care. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Global developmental delay; Disabilities; Anxiety; Alpha-amylase; Cortisol; Paediatric; Dental treatment